Analisis Resepsi Generasi Z terhadap Judi Online pada Kanal YouTube Ferry Irwandi - Randy Wiradharma; Kusuma, Ade (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Generation Z is highly active on social media, a trend amplified during the COVID-19 pandemic due to limited social interaction. Data from the Indonesian Internet Service Providers Association (APJII) reveals that Generation Z constitutes the majority of internet users (34.40%). This shift in communication behavior has brought convenience but also increased cybercrime. UU No 19 Tahun 2016regulates various cybercrime issues including online gambling. Indonesia has the highest number of online gambling users globally, with around 200,000 active users. Influencer Ferry Irwandi highlights the  seriousness of this issue on his YouTube channel, which featured three new videos on the topic in September 2023. His observations underline the need for further research into the impact of online gambling on Generation Z. This study employs a descriptive qualitative approach using Stuart Hall's reception analysis method, focusing on Generation Z. Data were collected through in-depth interviews and Focus Group Discussions (FGDs). The findings reveal Generation Z's reception of online gambling content on Ferry Irwandi's channel, identifying two primary perspectives: the Dominant-Hegemonic Reading Position and the Negotiated Reading Position. Generation Z recognizes online gambling as a pervasive, addictive, and destructive activity. They assert that influencers do not significantly contribute to its spread, emphasizing the importance of being selective about media consumption. Generation Z calls for decisive government action to address online gambling issues.